ChemInform Abstract: Rapid Oxidation of Organic Halides with N‐Methylmorpholine N‐Oxide in an Ionic Liquid under Microwave Irradiation. Issue 28 (21st June 2013) - Khumraksa, Bannarak; Phakhodee, Wong; Pattarawarapan, Mookda
Abstract Benzylic halides and primary alkyl bromides are readily converted into the corresponding carbonyl compounds.